Indonesian EFL Students’ Perception of Project Based Learning: A Focus on Gender and Learning Style - Wilda Nulhikmah; Rahmah Fitriani; Ahman Amin Dalimunthe (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aims to analyze students’ perceptions of the implementation of Project-Based Learning (PjBL) in English as a Foreign Language (EFL) classrooms at SMP Azzakiyah Islamic Leadership. Data were collected through semi-structured interviews, FIAC-based classroom observations, and self-assessment questionnaires. A qualitative approach was employed to identify patterns of student engagement and perceptions based on gender, learning styles, and language proficiency levels. Findings revealed that PjBL fostered a learner-centered environment, with student talk dominating classroom interaction at 57%, reflecting active collaboration and learner autonomy. Students perceived PjBL as a motivating and authentic learning approach that enhanced cooperation and communicative competence. Gender differences emerged in participation tendencies: female students emphasized collaborative and affective engagement, while male students preferred leadership and technical roles. Variations in learning styles (visual, auditory, kinesthetic) shaped students’ engagement modes, and proficiency levels influenced confidence and contribution within group projects.